P023 Investigating the clinical value of treponema pallidum PCR within a UK gum clinic. (8th June 2017) - Parsloe, Alice; White, David; Smit, Erasmus
Abstract : Introduction: Syphilis is a multistage STI caused by Treponema pallidum. The classic lesion of primary syphilis is a chancre – a single, painless, indurated ulcer with a clean base. The number of cases is on the rise, and it has been historically difficult to diagnose due to its variable presentation, requiring clinical correlation and multiple investigations. PCR use has increased recently in investigation of these ulcers. However, how crucial is PCR testing in primary syphilis, when cheaper investigations can lead to a diagnosis? Methods: Investigation results were collected from 58 patients presenting between January and December 2015 who were treated for primary syphilis, including presentation, serology and PCR status. How they were diagnosed as having primary syphilis was noted and whether this was on presentation, follow up or via PCR. Results: 47 patients had a positive PCR, 11 patients had a negative PCR but were treated for primary syphilis. We found 3 patients would have not been picked up as having primary syphilis if there was no PCR performed. The sensitivity and specificity of Treponema pallidum PCR was 81% and 100% respectively. Discussion: PCR was essential in diagnosing 3 patients with syphilis who would have been missed, therefore PCR is a crucial tool in contributing to the diagnosis of primary syphilis. The potential implications of missing syphilis diagnosis are serious, as patients can develop progressive disease and unknowingly affect sexual partners.